THE CONTENT OF RELIGIOUS INSTRUCTION IN EARLY TWENTIETH-CENTURY JADID TEXTBOOKS - Sobirov Zuhriddin Najmiddin ugli (International Journal of Literature and Language Studies, 2026)
This article analyses the place and content of religious instruction in the educational textbooks produced by the Turkestan Jadids in the early twentieth century. Drawing on the primers and religious-subject textbooks authored by Mahmudkhoja Behbudi, Munavvar Qori Abdurashidkhanov, Abdulla Avloni, and Saidrasul Saidazizi, the study demonstrates that the new-method (usul-i jadid) reform did not abolish religious teaching but rather reformed its methodology and content. The findings confirm that in Jadid maktabs, Qurʼanic literacy was taught through the phonetic method (usul-i savtiya), while creed, ritual practice, ethics, and the history of Islam were taught in the mother tongue — systematically and intelligibly. The author assesses the Jadid educational project as a movement of renewal (tajdid) within the Islamic tradition.